Informatikos mokslo objektas - Kancleris, Algirdas (Knygotyra, 1970)
It is possible to say that, roughly speaking, informatics is library science (and bibliography) equipped with exact methods of research and perfected technical tools, including computers.From the very beginning of civilization mankind conceived the need of recording. storing and retrieving of information. This was the cause that gave rise to written language, book publishing, libraries, information centres, etc. Libraries were organized on the basis of certain principles. But library science, theoretical and experimental, did not become a united and consistent science.After the Second World War, when the period of domination of mathematical methods and computers began, the necessity of revision of principal propositions of librarianship became evident. This gave rise to a new theoretical branch of science, whose subject was similar to that of library science. At the end of 1966 it was named „inlormatics“ in the U. S. S. R. This term was immediately accepted in Lithuania.The name and the object of informatics are widely discussed in Soviet and foreign publications. When describing the object of informatics clear and precise definition of the aim, sphere of investigation and basic methods of the science is necessary. The suggested description of the object of informatics is this:Informatics is a theoretical branch of science which, using exact methods, investigates into the laws of movement of scientific and technical information and develops optimal systems, directed at the information of the users.Informatics is a science which by means of a system of exact symbols tries to present a quantitative image, compare and evaluate variables, properties and relations of investigated processes and phenomena. It studies forms and ways of movement of scientific and technical information in space and time, laws of its transformation, etc. From the point of view of content informatics can be defined as a part of semantic information, related to the objects of science (revealing of new objects, processes or connexions in nature, society and thinking) and engineering (applying discovered laws to solving of particular problems in industry, etc.).Informatics does not confine itself to analysis of dynamics of information processes, but also tends to develop an optimal system for scientific and technical information of the users, managed and controlled on the basis of feed-back. The user is a central figure of this system, and the criterion for evaluating its activities. One of the basic problems of informatics is development of quantitative theory for measurement of content of information.Informatics is only in the state of development and searching for its trends. Therefore the definition of the object of its study must help in choice of the general trend of investigation.